A.W.D. Secret Service Bureau. Old North Church - Boston - Sampson & Murdock Co. (Tufts Archival Research Center, 2005)
Page image of A.W.D. Secret Service Bureau. Old North Church - Boston in The Boston directory for the year commencing August 1, 1925